The Multifaceted Seafarer: An Explorative Discourse Analysis of Seafarers’ Portrayals in Swedish Maritime Magazines - Magnus Boström (Ocean and Society)
Seafaring is a highly male‐dominated occupation. Within the industry, there is an ambition to increase the proportion of women working in maritime professions. In this endeavor, it is relevant to examine how seafarers are portrayed in various contexts. This study aimed to explore the image of seafarers as presented in Swedish maritime magazines: How are seafarers described, and can these descriptions be seen as performative in shaping a professional identity? To meet this aim, a discourse analysis was performed, based on 20 texts from two maritime magazines, representing both rating and officer seafarers. Overall, six subject positions inhabited by seafarers were identified, with several overlapping characteristics. For example, traits of the traditional seafarer were also found in the masculine seafarer and the flexible seafarer. Furthermore, it is argued that several of the subject positions are difficult to combine with what is referred to as the gender‐equal seafarer, mainly due to challenges in balancing family life with extended periods at sea. The study shows that today’s seafarers, according to how they are depicted in Swedish maritime magazines, have considerable agency in shaping their own professional identity without being forced to conform to a hegemonic masculinity. Finally, it is suggested that the term “seafarer” be used instead of “seaman” in both print and everyday conversations, for increased inclusiveness and representation.